Higher predation risk for insect prey at low latitudes and elevations - Roslin, T; Hardwick, B; Novotny, V; Petry, W; Andrew, N; Asmus, A; Barrio, I; Basset, Y; Larissa Boesing, A; Bonebrake, T; Cameron, E; Dátillo, W; et al. (American Association for the Advancement of Science, 2017)
Biotic interactions underlie ecosystem structure and function, but predicting interaction outcomes is difficult. We tested the hypothesis that biotic interaction strength increases towards the Equator, using a global experiment with model caterpillars to measure predation risk. Across an 11,660 km latitudinal gradient spanning six continents, we found increasing predation towards the Equator – with a parallel pattern of increasing predation towards lower elevations. Patterns across both latitude and elevation were driven by arthropod predators, with no systematic trend in attack rates by birds or mammals. These matching gradients at global and regional scales suggest coherent drivers of biotic interaction strength, a finding which needs to be integrated into general theories of herbivory, community organization, and life history evolution.